2005
DOI: 10.1149/1.1885365
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ta[sub 2]O[sub 5] and Nb[sub 2]O[sub 5] in Bilayered Structures and Solid Solutions for Use in MIM Capacitors

Abstract: Binary systems of Ta 2 O 5 and Nb 2 O 5 are investigated as dielectric materials that allow low-temperature fabrication and are suitable for use in metal-insulator-metal ͑MIM͒ capacitors. This investigation shows that a Nb 2 O 5 film is crystallized in a hexagonal symmetry at a temperature of less than 500°C, which is more than 250°C lower than the corresponding temperature for a Ta 2 O 5 film. Using Nb 2 O 5 as a nucleation layer lowers the crystallization temperature for Ta 2 O 5 to less than 500°C. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
1
21
1
Order By: Relevance
“…Note that the corresponding original patterns are demonstrated in Supporting information Figures S4 and S5. Owning to the same orthorhombic lattice structure, similar lattice parameters and metal ionic radius (0.74 Å) of Nb 2 O 5 and Ta 2 O 5 (Supporting information Table S4) 58 , oxidized (Nb 0.5 Ta 0.5 )C comprises 5, also confirm this phenomenon. However, the I 1(o) /I 2(m) value measured from oxidized (Hf 0.5 Nb 0.5 )C is apparently higher than that determined from (Hf 0.5 Ta 0.5 )C at each oxidation temperature, indicating a more remarkable stimulative effect of Nb than Ta.…”
Section: (I) the Phase Composition Of Carbide Solid Solutions After O...supporting
confidence: 63%
See 1 more Smart Citation
“…Note that the corresponding original patterns are demonstrated in Supporting information Figures S4 and S5. Owning to the same orthorhombic lattice structure, similar lattice parameters and metal ionic radius (0.74 Å) of Nb 2 O 5 and Ta 2 O 5 (Supporting information Table S4) 58 , oxidized (Nb 0.5 Ta 0.5 )C comprises 5, also confirm this phenomenon. However, the I 1(o) /I 2(m) value measured from oxidized (Hf 0.5 Nb 0.5 )C is apparently higher than that determined from (Hf 0.5 Ta 0.5 )C at each oxidation temperature, indicating a more remarkable stimulative effect of Nb than Ta.…”
Section: (I) the Phase Composition Of Carbide Solid Solutions After O...supporting
confidence: 63%
“…Note that the corresponding original patterns are demonstrated in Supporting information Figures S4 and S5. Owning to the same orthorhombic lattice structure, similar lattice parameters and metal ionic radius (0.74 Å) of Nb 2 O 5 and Ta 2 O 5 (Supporting information Table S4) 58 , oxidized (Nb 0.5 Ta 0.5 )C comprises orthorhombic (Nb x Ta 1‐x ) 2 O 5 solid solution with single‐phase and homogenous element distribution (Supporting information Figure S6), besides, at different time durations the phase remains stable, as depicted in Supporting information Figure S7. It can be concluded that compared with pristine NbC, the doping of TaC can restrain the high‐temperature transition of Nb 2 O 5 from orthorhombic to monoclinic.…”
Section: Resultsmentioning
confidence: 85%
“…Niobium oxide has a higher dielectric constant (ε = 53) with respect to Ta 2 O 5 but a lower band gap (∼3.3 eV). In recent papers, [1][2][3] it has been shown that the addition of small amount of Nb in tantalum based oxide decreases the crystallization temperature with small effect on the band gap value of the material. Thus, (Nb (1−x) Ta x ) 2 O 5 have been introduced in the International Technology Roadmap for Semiconductors (ITRS).…”
mentioning
confidence: 99%
“…15 It is important to understand how Ru reacts with NaIO 4 slurry solutions and forms the passivation layer. Figure 1 shows the Eh-pH diagram of the Ru-H 2 Figure 2 shows the static etch rate and passivation film thickness as a function of NaIO 4 concentration. The static etch rate and passivation film thickness of Ru increased with an increase in NaIO 4 concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, a metal-insulator-metal capacitor has been investigated. 1,2 Noble metals can be used as bottom electrodes of capacitors because they have a high work function, and thus provide a high barrier for leakage current. In addition, they are chemically very stable.…”
mentioning
confidence: 99%